Sex and Cognitive Style: Research Artefact or Regularity? - E V Belovol (Peoples' Friendship University of Russia (RUDN University), 2011)
The analysis of the results of sex differences in cognitive styles study for the past 60 years is presented in the article. The absence of the unified accepted point of view on the problem is revealed. The assumption that such inconsistent and conflicting results are partly due to the inadequate statistical methods used for these hypotheses verification is substantiated.